Analysis of the Implementation of Restorative Justice in Domestic Violence Crimes - Risman Risman (Public Resource Innovation Management and Excellence, 2024)
Domestic violence is actually any act against a person, especially women, which results in physical, sexual, psychological misery or suffering and/or neglect of the household including threats to commit acts, coercion or unlawful deprivation of liberty within the scope of the household. The purpose of this study is what form of restorative justice approach and efforts to implement the concept of restorative justice approach in handling cases of domestic violence. The research method used is a normative legal research method using a statutory and conceptual approach. The restorative justice approach is realized through dialogue between parties known as